2020
DOI: 10.32615/ps.2019.182
|View full text |Cite
|
Sign up to set email alerts
|

Silicon improves the photosynthetic performance of black pepper plants inoculated with Fusarium solani f. sp. piperis

Abstract: This study evaluated the effect of silicon (Si)-supplementation in controlling the fusariosis in two Piper nigrum cultivars (Bragantina and Kottanadan). We hypothesized that susceptible cultivar improves the photosynthetic performance with Si-supplementation. Under greenhouse conditions, six-month-old plants were treated with silicon 30 and 15 d before inoculation with Fusarium solani f. sp. piperis and compared with untreated plants and with healthy control plants. All samples remained photosynthetically acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 59 publications
(54 reference statements)
0
6
0
Order By: Relevance
“…Fusarium infection also alters physiological responses and reduces stomatal conductance and transpiration in tomato plants, while application of PBE-1 enhances transpiration and stomatal conductance during Fusarium infection, as the xylem responsible for the passage of water is not blocked. Fernandes et al (2020) also reported that Fusarium infection results in reduce gs and transpiration.…”
Section: Discussionmentioning
confidence: 92%
“…Fusarium infection also alters physiological responses and reduces stomatal conductance and transpiration in tomato plants, while application of PBE-1 enhances transpiration and stomatal conductance during Fusarium infection, as the xylem responsible for the passage of water is not blocked. Fernandes et al (2020) also reported that Fusarium infection results in reduce gs and transpiration.…”
Section: Discussionmentioning
confidence: 92%
“…Photosynthetic performances were enhanced by the application of a Si supplement to dicot plants such as black pepper where it reduced disease severity and improved resistance to Fusarium solani f. sp. piperis (D'Addazio et al, 2020). Furthermore, Si application alleviated water stress by modulating some photosynthesis‐related genes, regulating the photochemical process and reducing the effects of iron toxicity (dos Santos et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Photosynthetic performances were enhanced by the application of a Si supplement to dicot plants such as black pepper where it reduced disease severity and improved resistance to Fusarium solani f. sp. piperis(D'Addazio et al, 2020). Furthermore, Si application alleviated water stress by…”
mentioning
confidence: 95%
“…Changes in leaf photochemistry and carbon metabolism are often associated with the lower activity of Rubisco and changes in the capacity for regeneration of ribulose-1,5-bisphosphate (Hiscox and Israelstam, 1979). The reduction in Rubisco's activity has also been reported in plants infested with pathogens (Dꞌaddazio et al, 2020).…”
Section: Discussionmentioning
confidence: 99%